Delayed-Expansion Capsule Sealing Material for Coal Mine Overburden Isolated Grouting - Dayang Xuan; Xiaoming Ning; Kaifang Lu; Jian Li; Jialin Xu (Applied Sciences)
Grouting technology is an important method of ground reinforcement and can effectively improve the stability of engineering rock mass. During overburden isolated grouting in coal mines, the influence of unexpected fractures may lead to substantial grout leakage, resulting in ineffective grouting. The existing natural sedimentation sealing method is mainly applicable to small fractures and low grout flow, while the chemical-reagent rapid-sealing method can cause grouting channel blocking, making it less suitable for overburden isolated grouting. This paper proposes a “capsule” sealing method, detailing the preparation of the sealing material and evaluation of its properties through testing. The sealing material, prepared using the air suspension method, was coated with paraffin on a superabsorbent polymer (SAP) material, which has delayed expansion characteristics. Although this material does not expand within the grouting fractures of overburden rock, it expands rapidly upon entering the leakage channel, accumulating within the channel to achieve effective sealing. A simulation experimental system was designed to simulate the sealing of the slurry leakage channel, and the sealing characteristics were experimentally investigated. Under consistent particle size conditions, a higher film cover ratio led to a more pronounced delayed expansion effect and extended the time required for the sealing material to achieve its maximum expansion. When the content of sealing material with particle sizes of 20 mesh, 40 mesh, and 60 mesh, and a film ratio of 20% was 1.0%, the fractures below 4 mm were effectively sealed. When the fracture aperture is 4–6 mm, the sealing material with a covering ratio of 20% or 30% should have a minimum content of 1.5%, while the sealing material with a covering ratio of 50% should have a minimum content of 2.0%. The findings of this study outline an effective prevention and control method for the sealing of abnormal slurry leakage in overburden isolated grouting engineering.